Maturation of the 90S pre-ribosome requires Mrd1 dependent U3 snoRNA and 35S pre-rRNA structural rearrangements. Issue 7 (24th January 2018) - Lackmann, Fredrik; Belikov, Sergey; Burlacu, Elena; Granneman, Sander; Wieslander, Lars
Abstract: In eukaryotes, ribosome biogenesis requires folding and assembly of the precursor rRNA (pre-rRNA) with a large number of proteins and snoRNPs into huge RNA-protein complexes. In spite of intense genetic, biochemical and high-resolution cryo-EM studies in Saccharomyces cerevisiae, information about the structure of the 35S pre-rRNA is limited. To overcome this, we performed high-throughput SHAPE chemical probing on the 35S pre-rRNA within 90S pre-ribosomes. We focused our analyses on external (5′ETS) and internal (ITS1) transcribed spacers as well as the 18S rRNA region. We show that in the 35S pre-rRNA, the central pseudoknot is not formed and the central core of the 18S rRNA is in an open configuration but becomes more constrained in 20S pre-rRNA. The essential ribosome biogenesis protein Mrd1 influences the structure of the 18S rRNA region locally and is involved in organizing the central pseudoknot and surrounding structures. We demonstrate that U3 snoRNA dynamically interacts with the 35S pre-rRNA and that Mrd1 is required for disrupting U3 snoRNA base pairing interactions in the 5′ETS. We propose that the dynamic U3 snoRNA interactions and Mrd1 are essential for establishing the structure of the central core of 18S rRNA that is required for processing and 40S subunit function.